2005
DOI: 10.1097/01.wnr.0000181586.49130.48
|View full text |Cite
|
Sign up to set email alerts
|

Postural constraints to coupling of ipsilateral hand–foot movements

Abstract: Ipsilateral hand and foot are easily coupled in isodirectional oscillations, while antidirectional coupling is difficult or even impossible. It was recently suggested that differences between the two types of coupling depend on the interaction of postural mechanisms with voluntary movement. We report here that when standing in an upright position, with the right hand touching a rigid support and the right foot fixed to a tilting platform, fast foot flexions or extensions as well as rhythmical foot oscillations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
5
20
0
Order By: Relevance
“…Although in the latter case generation of the APAs command seems to be uneconomical, it highly simplifies and speeds up the postural control, which only requires a gain adjustment at each potential fixation chain (Esposti and Baldissera 2011). This result also confirms two previous observations in which cortical excitability of resting hand movers has been shown to fluctuate under threshold for the motoneuronal firing when the ipsilateral foot is voluntarily oscillated (Baldissera et al 2002) and in which the ''hidden effect'' develops in an overt APA once the hand is recruited in a postural act (Baldissera and Esposti 2005).…”
Section: Introductionsupporting
confidence: 88%
“…Although in the latter case generation of the APAs command seems to be uneconomical, it highly simplifies and speeds up the postural control, which only requires a gain adjustment at each potential fixation chain (Esposti and Baldissera 2011). This result also confirms two previous observations in which cortical excitability of resting hand movers has been shown to fluctuate under threshold for the motoneuronal firing when the ipsilateral foot is voluntarily oscillated (Baldissera et al 2002) and in which the ''hidden effect'' develops in an overt APA once the hand is recruited in a postural act (Baldissera and Esposti 2005).…”
Section: Introductionsupporting
confidence: 88%
“…In fact, the tDCS selective action upon one of the two components suggests that the shared command is generated at a higher hierarchical level than SMA. Considering that SMA receives thalamic projections and that its stimulation elicits sensory effects (Nachev et al, 2008), it might be inferred that the SMA receives information for APAs modulation, like the postural context in which the movement occurs (Cordo & Nashner, 1982;Dietz & Colombo, 1996;Baldissera & Esposti, 2005;Esposti & Baldissera, 2011), and tailor the APAs consequently.…”
Section: Sma and Posturementioning
confidence: 99%
“…It has been recently shown that in sitting volunteers performing voluntary foot (Baldissera et al, 2002) or contralateral wrist (Carson et al, 2004) flexions/ extensions, the excitability of corticospinal pathways targeting the resting wrist muscles is modulated in phase with movements, whereas the H-reflex and f-waves are depressed markedly during contraction of homologous muscles of the contralateral forearm (Hortobágyi et al, 2003;Carson et al, 2004). Moreover, in standing subjects, overt electromyographic activity in forearm muscles has been described to accompany movements of the contralateral forearm (Slijper and Latash, 2000) or ipsilateral foot (Baldissera and Esposti, 2005). These complex functional changes are probably a result of highly stereotyped connections, which are therefore likely to exert their effects even under conditions in which a manifest postural intervention is not required, as when subjects lie supine in the restrained environment of the fMRI scanner.…”
Section: Side Differences In Motor-related Fmri Spinal Signalsmentioning
confidence: 99%